2023
DOI: 10.1007/s12594-023-2288-y
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Land Cover (LULC) and Surface Water Quality Assessment in and around Selected Dams of Jharkhand using Water Quality Index (WQI) and Geographic Information System (GIS)

Abstract: Surface water quality deterioration is mainly occurring due to anthropogenic activities at an alarming rate in developing countries. Jharkhand has been undergoing exponential urbanisation and mining, causing immense surface water pollution and water stress. The state is heavily dependent on artificial dams for its daily water supply demands. Therefore, an effort is made to monitor and ascertain the surface water quality and the influence of nearby land use pattern on water quality, in the selected five dams, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…Given the range of pollutants associated with LULC transformations, several studies have used WQIs to translate the observed measurements of multiple parameters into a single unitless score of overall water quality (e.g., Schiff & Benoit, 2007;Shukla et al, 2018;Wang & Zhang, 2018;Gossweiler et al, 2019;Umwali et al, 2021;Paná et al, 2022;Pandey et al, 2023). In the present study, the NPI provided a convenient means of quantifying overall pollution levels across the sample of 58 sub-catchments.…”
Section: Water Quality Analysismentioning
confidence: 95%
“…Given the range of pollutants associated with LULC transformations, several studies have used WQIs to translate the observed measurements of multiple parameters into a single unitless score of overall water quality (e.g., Schiff & Benoit, 2007;Shukla et al, 2018;Wang & Zhang, 2018;Gossweiler et al, 2019;Umwali et al, 2021;Paná et al, 2022;Pandey et al, 2023). In the present study, the NPI provided a convenient means of quantifying overall pollution levels across the sample of 58 sub-catchments.…”
Section: Water Quality Analysismentioning
confidence: 95%
“…As no single water quality parameter can provide a sufficiently comprehensive overall measure of water quality, aggregate water quality indices (WQIs) have been used in several studies to evaluate the impacts of LULC on water quality (Shukla et al, 2018;Wang & Zhang, 2018;Kim et al, 2020;Gani et al, 2023;Pandey et al, 2023;Zhang et al, 2023). Concomitantly, Nemerow's Pollution Index (NPI) was used in the present study to assess the overall degree to which water quality in each of the selected sub-catchments had been impacted by surrounding LULC changes.…”
Section: Nemerow's Pollution Indexmentioning
confidence: 99%
“…This is partly because existing empirical studies that do investigate temporal associations between land use change and downstream water quality have limitations that influence the generalization of their findings. For example, many are geographically constrained to either a single watershed or smaller geographic regions (Meneses et al., 2015; Pandey et al., 2023; Risal et al., 2020; Smith et al., 2015; Wang et al., 2023; Wijesiri et al., 2018). While these geographically limited studies provide valuable insights, their applicability is constrained to their unique geomorphologic, anthropogenic, and climatic contexts.…”
Section: Introductionmentioning
confidence: 99%